Dear England: finding hope, taking heart and changing the world - Cottrell, Stephen (Hodder & Stoughton, 2021)
"Dear England is the story of how Christian faith can make sense of life, giving a framework fo how we deal with our biggest questions and deepest longings; and how its values and ideals can shape the way we live - and bring change to - the world. Written without resorting to individual experience or religious jargon, Dear England clears the obstacles that can get in the way of faith for those who, like its author, were brought up in a secular world, and haven't had the opportunity to think clearly abou the claims of faith. Both contemplative and deeply practical, this is an invitation to reconsider the Christian hope of a changed heart - and a changed world"--Pag 2 of book jacket